2014
DOI: 10.1109/ted.2014.2359994
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Static Thermal Coupling Between Emitter Fingers of Bipolar Transistors

Abstract: A strategy for compact modeling the static thermal coupling between the emitter fingers of SiGe heterojunction bipolar transistors (SiGe-HBTs) is described. An extraction methodology that includes the nonlinear temperature dependence of the thermal conductivity is introduced and applied to suitable test structures. The experimental results are used for calibrating a 3-D numerical solution of the equation for heat conduction based on a Green's function approach. The latter can then be employed for generating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…It is observed that the high-V BE curves (0.9 V and 0.95 V) exhibit significant effects of electro-thermal heating. Also the predictions of the state-of-the-art thermal model of [6] [5] are identical with the results of our model. This proves that our model implementation indeed preserves the physical basis of [5].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…It is observed that the high-V BE curves (0.9 V and 0.95 V) exhibit significant effects of electro-thermal heating. Also the predictions of the state-of-the-art thermal model of [6] [5] are identical with the results of our model. This proves that our model implementation indeed preserves the physical basis of [5].…”
Section: Resultssupporting
confidence: 80%
“…2 does not use any VCVS in its implementation. Although the reduction in complexity for n = 2 is not visible, it is quite significant for n = 5 which requires only 10 extra nodes in our model in contrast to 25 extra nodes in conventional approach [5] [6]. In case of discarding the thermal coupling and considering only the selfheating effect in a multi-finger transistor simulation (which is very much unlikely), our approach still uses 2n extra nodes whereas the conventional approach uses only n extra nodes since the nodes across the VCVS (with 0 V) will collapse.…”
Section: Model Formulation and Implementationmentioning
confidence: 87%
See 1 more Smart Citation
“…The reduction of c ij with increasing P diss is due to the positional temperature-dependent thermal conductivity of silicon within the device. The same trend has been reported in other works such as [17,18,20]. For the multifinger device housed within DT, we employed the thermal spread model as detailed in Section 2.4 considering adiabatic boundary conditions at DT [13] to estimate ∆T jj,dt .…”
Section: Resultsmentioning
confidence: 98%
“…Figure 2b shows that in case of shallow trench isolated (STI) multifinger structures, the model of [19] yields further erroneous results for c ij with maximum error of around 57% when compared with 3D TCAD simulation. Note that following the standard practice, c ij is represented in percentage which is obtained by multiplying Equation (2) by 100 [17,18,20]. The poor modeling results in Figure 2a,b indicate the importance of using a temperature dependent thermal conductivity in the modeling framework and further to include the specific effects originating from the trench-isolations.…”
Section: Introductionmentioning
confidence: 99%